Evidence of convergence or divergence: an analysis of the behavior of the economies of the states of the Brazilian Midwest region - 1985 to 2019) (Research, Society and Development, 2022)
Over time, economic growth has presented unevenly across countries, creating an increase in the degree of inequality between the poorest economies and the richest. In a regional perspective, this phenomenon also occurs with regions of the same country that are richer than the others. Economic inequalities also imply different qualities of life, which translate into unequal survival conditions. The main reason for this research is to investigate possible evidence of convergence of the economies of the states of Goiás, Mato Grosso and Mato Grosso do Sul, with the state of São Paulo. Through econometric techniques it was possible to estimate the results of the betas. Far from reaching definitive results, this article proposes to open a discussion about what would be happening with the per capita income of these states in relation to the São Paulo economy. For the execution of this work, data from IBGE and IPEADATA from 1985 to 2019 were used.